107-6x=9x-45+2

Simple and best practice solution for 107-6x=9x-45+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 107-6x=9x-45+2 equation:



107-6x=9x-45+2
We move all terms to the left:
107-6x-(9x-45+2)=0
We add all the numbers together, and all the variables
-6x-(9x-43)+107=0
We get rid of parentheses
-6x-9x+43+107=0
We add all the numbers together, and all the variables
-15x+150=0
We move all terms containing x to the left, all other terms to the right
-15x=-150
x=-150/-15
x=+10

See similar equations:

| 5^12-4x=625 | | 12x-2=2x+14 | | 4=(12x-5) | | 107-6x+9x-45+2=180 | | 5^(12-4x)=625 | | 5c+22=52 | | 75-v=50 | | -2x+17=33 | | -7+4t=-15 | | (x/2-12=24 | | -8-7n=32+3n | | 2(5^x)=18 | | 0=25x+72 | | x+8x-7=74 | | 10=2b+17 | | Y=-16x^2+200x+82 | | 3.x+2.6=-23 | | 2n+10=-6 | | B+6/9=b/3 | | 8y+14=5y+6-10 | | 13=5m-4-6m | | 12=4-5p | | 4x-2=5+3(2x+1 | | -t+14=-22 | | b-6/9=b/3 | | x=-2+8/11 | | X+0.17x=9 | | 8+p=26 | | e-4=-4 | | -2n+6=24 | | 8x-41+6x+1=180 | | 6(c-13)=-36 |

Equations solver categories